Pitch range declination and reset in turn-taking organisation - Yanushevskaya, Irena (My University, 2014)
This paper examines how pitch range declination and reset contribute to turn-taking organisation. This is part of a broader study of voice prosody, i.e., how pitch, voice quality and temporal features combine for various prosodic functions, both linguistic and paralinguistic. The present study first investigates the effect of the speech unit position in a turn on its pitch range. We also test the effect of the number of speech units in a turn as well as the turn duration on the turn-initial f 0 peak height at the beginning of the turn. Our results suggest a pitch range declination trend between the Initial and Median speech units of a turn but a violation of this declination for the Final units of the turn. They also demonstrate that the higher the number of speech units in a turn or the longer the turn, the higher the turn-initial f 0 peak height. We discuss our findings along the debate on Projection and Reaction theories and that of Hard vs. Soft pre-planning of speech production. We address how these findings may be useful to formulate a holistic model of prosody and to enhance human-machine interactions.
Speech Prosody 7
Keywords: Hard vs. soft pre- planning; Pitch range; Declination; Reset; Pause; Gap; Turn-taking; Reaction vs. projection theories